Distribution of Legionella species and serogroups in patients with culture-confirmed Legionella pneumonia. Issue 5 (May 2020) - Miyashita, Naoyuki; Higa, Futoshi; Aoki, Yosuke; Kikuchi, Toshiaki; Seki, Masafumi; Tateda, Kazuhiro; Maki, Nobuko; Uchino, Kazuhiro; Ogasawara, Kazuhiko; Kiyota, Hiroshi; Watanabe, Akira
Abstract: Legionella species are consistently identified as some of the most common causative agents of severe community-acquired pneumonia (CAP) or nosocomial pneumonia. Although the number of reported Legionella infection cases is gradually increasing in Japan, most cases are diagnosed by a urinary antigen test, which identifies only L. pneumophila serogroup 1. Therefore, assessment of pneumonia-causing Legionella species and serogroups would be important. The Japan Society for Chemotherapy Legionella committee has collected the isolates and clinical information on cases of sporadic community-acquired Legionella pneumonia throughout Japan. Between December 2006 and March 2019, totally 140 sporadic cases were identified, in which L. pneumophila was the most frequently isolated species (90.7%) followed by L. bozemanae (3.6%), L. dumofii (3.6%), L. micdadei (1.4%), and L. longbeachae (0.7%). Among 127 isolates of L. pneumophila, 111 isolates were of serogroup 1, two of serogroup 2, four of serogroup 3, one of serogroup 4, one of serogroup 5, seven of serogroup 6, and one was of serogroup 10. We also assessed in vitro activity of antibiotics against these isolates and showed that quinolones and macrolides have potent anti- Legionella activity. Our study showed that pneumonia-causing Legionella species and serogroup distribution was comparable to that reported in former surveillances. L. pneumophila was the most common etiologic agent in patients with community-acquired Legionella pneumonia, and L. pneumophila serogroup 1 was the predominant serogroup.